A STUDY ON THE HAZARD OF ERUPTION AND LANDSLIDE IN INTERVOLCANIC BASIN OF MERAPI-MERBABU CENTRAL JAVA - Nurhadi Nurhadi; Arif Ashari; Suparmini Suparmini (Jurnal Penelitian Saintek, 2015)
This study aimed to: (1) assess the eruption and landslide hazard, and (2) create a map of the spatial distribution of hazard in intervolcanic basin of the Merapi-Merbabu, Central Java Province. The method employs in this research was exploratory surveys, with regional complex approach. The population in this study were all landscape phenomena between intervolcanic basin of Merapi-Merbabu, located in parts of sub-district Sawangan, Magelang District, and sub-district Selo, Boyolali District. Sample was determined by observation of purposive sampling technique that at each terrain unit. Data collecting was carried out with observation, interpretation of remote sensing imagery, literature review, and documentation. The analysis used GIS analysis, scoring analysis, supported by descriptive analysis. The results showed the hazard of volcanic eruption varies between moderate to high. Moderate hazard exist in the area of Merbabu Volcano, while high hazard exist in the area of Merapi Volcano. High hazard mainly affected by high level of distance from active crater of Merapi Volcano and slope. The landslide hazard varies between very low to moderate. Very low and low hazard exist in the area of Merapi Volcano, while moderate hazard exist in the area of Merbabu Volcano. Moderate hazard mainly affected by high level of slope, soil texture, soil depth, and vegetation density.